Managerial economics economic tools for today's decision makers - Keat, Paul G.; Young, Philip K. Y.; Erfle, Stephen E. (Stephen Eugene) (Pearson Education Limited, 2014)
For upper-level undergraduate and first-year MBA courses in managerial and applied economics. This Global Edition has been edited to include enhancements making it more relevant to students outside the United States This text will excite readers by providing a more linear progression, while proving the consistency and relevance of microeconomic theory. The Seventh Edition welcomes a new co-author, Stephen Erfle of Dickinson College, who has contributed many revisions and improvements to the quantitative sections of the text